Railway Axle Analyses: Fatigue Damage and Life Analysis of Rail Vehicle Axle - Dikmen, Ferhat; Bayraktar, Meral; Guclu, Rahmi (ASSOC MECHANICAL ENGINEERS TECHNICIANS SLOVENIA, 2012)
In this study, failures in axles of rail vehicles have been examined. The axle failure in the paper is a classic fatigue problem with high magnitude bending stresses which alternate between tension and compression. The scope of this paper is to address life value of axle related to reliability and compare it with the realized life value up to fracture. The activity firstly deals with the definition of critical section in the axle. The location of the fracture is the section between the wheel and gear. The research then addresses determination of the wagon loading cases based on statistical data related to the number of passengers. First, minimum life value of the axle was determined considering full load, then effective life values were calculated by using Palmgren- Miner's theorem as a cumulative failure theorem for real loading conditions in the case of different distributions. It is apparent from data found by calculations are in good agreement with practical damage values. Finally, changing of effective life values related to different working conditions is presented.
Keywords: rail vehicle axle; fatigue; cumulative failure; life; reliability; Engineering